Uncomplicated Appendicitis In Paediatrics Patients- Evaluate Outcome Of Surgical Or Non-Surgical Management - Sharma, Ayushi; Ratre, Geetesh; Kumar Chopra, Ashok; Mathur, Geetika (Journal of Neonatal Surgery, 2025)
Introduction: Appendicitis most common abdominal surgical emergency in children with a lifetime risk of 8%. it accounts for over 11% of paediatric emergency room visits. Surgical management has been the mainstay of treatment over the years, however Non-surgical managemet has gained the popularity in recent years. Aim: uncomplicated appendicitis in paediatrics patients- evaluate outcome of surgical or non-surgical management. Materials and method: this is a prospective observational study done over a period of 3 years (January 2022-January 2025) in SMS Medical college, Jaipur were studied. Data of all chidren [less than 18 years of age] admitted for acute appedicitis (complicated/uncompliacted) over a period of 3 years. Diagnosis, mode of management i.e. surgical or conservative, post operative course/complications and duration of stay were redorded. Results: A total of 300 children (200 male / 100 female) were admitted for acute appendicitis over 2 years i.e. January 2022-January 2024. Uncomplicated appendicitis was seen in 250 (83.3%) patients. 200 of them underwent non-surgical while 50 were operated for persisting symptoms and clinical illness. Complicated appendicitis was found in 50 (16.6%) cases which were further operated and were excluded. Out of 50 surgically managed cases 40 had a history of prolonged conservative management elsewhere while 10 patients did not show any clinical relief even after a conservative management of a mean 5 days. The mean duration of stay in the non-surgical group was 2.7 days as compared to a longer mean duration of 8 days in the operative group. The mean duration to full feeds was longer in operative group (6 days) As compared to the non-surgical group (2.5 days). Recurrent appendicitis leading to surgical management was seen in 30/250 (12%) patients. Conclusion: So, finally from this study we concluded that non-surgical management lessens the operative costs and post- operative morbidity , hospital stay and its complications. a conservative management must be the first line of treatment for uncomplicated appendcitis.